The more ambidexterity the better? The moderating effect of organizational learning between high-performance HR practices and organizational performance - Wang, Canhao; Zhang, Meng; Ma, Hongtao (Frontiers in Psychology, 2024)
Objective The objective of this study is to test the directly impact of high-performance HR practices on organizational performance, and the mediating effect of organizational ambidexterity empirically. Moreover, the moderating role of organizational learning in the relationship between ambidexterity and specialization in exploitation or exploration on firm performance has also been examined. Ultimately, we construct a moderated mediation model. Methods Questionnaires were distributed to the target enterprises mainly through the contacts of the research group members, the local management consulting association and the training opportunities for leaders. Finally, a total of 347 CEO questionnaire data were collected from Chinese SMEs. The sample cover Shanghai, Beijing, Chongqing, Jiangsu, Zhejiang, Guangdong, Henan, Sichuan and other eastern and central regions. SPSS 23.0 and AMOS 24.0 were used to analyze the data. Results The results revealed that high-performance HR practices had a positive effect on organizational performance and that organizational ambidexterity played a partially mediating role between high-performance HR practices and organizational performance. Further, organizational learning moderated the effects of organizational ambidexterity and organizational specificity on firm performance. Discussion This study provided valuable practical insights. On one hand, this study provides a concrete operational scheme for SMEs in China to realize organizational ambidexterity by integrating a series of HR practices such as employees’ ability, motivation and opportunity. On the other hand, through organizational ambidexterity, firms can not only obtain organizational long-term performance by enhancing their new product R & D capabilities, that is, exploratory innovation, but also utilize their existing resources to improve and expand their existing products and services, that is, to achieve short-term performance by exploitative innovation.